Analysis Turn Around Time C03-Check Package on Airbus A320-200 - Rahmawati, Fajar Khanif; Prakoso, Suyudi Imam (Sekolah Tinggi Teknologi Adisutjipto, 2019)
Aircraft maintenance is one of the consequences due to aircraft utilization. C03-check package on an Airbus A320-200 aircraft is one of the scheduled maintenance with interval every 22,500 flight hours, or 15000 flight cycles, or 72 months whicever comes firts. As one of scheduled maintenance, the planning of maintenance activities must be planned as well as possible to make activities carried out efficiently and effectively in terms of time and resources. Preliminary data to make the planning is sourced from the MPD (maintenance planning document).The data included of the scope of work, manhours, and man power. The data obtained is processed using the CPM (Critical Path Method). The results of data processing, it is obtained that the C03-check package on the Airbus A320-200 aircraft takes 4 (four) days, with the critical path on the AD-D1-D2-D3-D4-D4-D5-D6-D7-G aircraft, in the area empenage access panel with the number of hours needed is 41.3 hours.